(untitled) (Research, Society and Development, 2021)
This work aimed to report an experience involving the application of a Didactic Sequence (DS) integrating chemistry contents to environmental themes for High School Students (HSS). The activities were developed in a public school, located in Encanto City, High West’ region, in the State of Rio Grande do Norte, with students enrolled in the 3rd grade of HSS. Aiming to provide an effective and satisfactory in organic functions’ contents and their relationship with the environment, the didactic sequence was structured in 05 steps: I) Survey of students’ prior knowledge; II); Field lesson in Encanto’ River; III) Expositive-dialogical classes addressing contents of chemistry and the environment; IV) Elaboration of educational-environmental posters; V) Socialization of elaborated materials. Through this lived experience, it is believed that the inclusion of environmental themes associated with Chemistry classes, allows students to be sensitized to local environmental issues, thus becoming critical and conscientious citizens, intervening in the social environment of their experience with social and environmental practices, innovative, transforming and sustainable.